The evaluation of the elastic properties of the arterial wall by ultrasonic study data in patients with atherosclerotic vascular lesions - Kostylev, M V; Grigorash, G A; Egorova, O N; Mishalov, V G; Smorzhevskiĭ, V I (Klinična hìrurgìâ (Kiïv), 1997)
Ultrasonic scanning method in a real scale of time was used in examination of 10 patients with abdominal aorta (AA) aneurysm, 10-with arterial hypertension (AH), 10-with obliterating atherosclerosis of the lower extremities vessels (OALEV) without AH and practically healthy controls aged 32-45 years. AA aneurysm and OALEV diagnosis was made according to the ultrasonic investigation and roentgen-contrast angiography data obtained. The statistically significant (P < 0.05) reduce of AA wall distentivity and its rigidity increase was disclosed while there were no differences of the values of vessel diameter, normalized for the body surface square, determined by the measured magnitude of the relative vessels deformation caused by the pulse change in arterial pressure. The changes of the vascular wall elastic-viscositive properties in patients with OALEV and AH were directed similarly but they lacked intensity. The AA aneurysm magnitude did not correlate with the degree of vascular wall distentivity (r = 0.46).